RATIONALITY OF ANTIBIOTIC PRESCRIPTIONS AMONG OUTPATIENTS IN THE INTERNAL MEDICINE CLINIC AT PERSAHABATAN GENERAL HOSPITAL JULY–SEPTEMBER 2023 - Artanti, Astrid Nada; Maria, Ima; Rahmi, Eldiza Puji; Citra Pradana, Dhigna Luthfiyani; Diliana, Diliana (Medika Kartika : Jurnal Kedokteran dan Kesehatan, 2025)
Antibiotic use has increased in both developing countries, such as Indonesia, and developed countries, such as Japan and Australia. This trend may lead to a rise in antibiotic resistance if antibiotics are used irrationally. This study aimed to evaluate antibiotic prescribing patterns using the Gyssens method among adult outpatients in the Internal Medicine Clinic at Persahabatan General Hospital during the period of July–September 2023. This was a descriptive study with a cross-sectional design. Data were collected retrospectively from the medical records of adult outpatients attending the Internal Medicine Clinic during the study period. Of the 30 patient records that met the inclusion and exclusion criteria, the age group 51–60 years represented the largest proportion of antibiotic prescriptions (46.67%). Levofloxacin was the most frequently prescribed antibiotic (30.3%). Based on the Gyssens method, 88.8% of prescriptions were classified as rational, while 11.1% were irrational. In conclusion, 88.8% of antibiotics prescribed for adult outpatients in the Internal Medicine Clinic at Persahabatan General Hospital during July–September 2023 were deemed rational according to the Gyssens method. Keywords : antibiotics, gyssens method, outpatient DOI : 10.35990/mk.v8n4.p400-411